As espacialidades em montagem no cinema e na televisão - Nakagawa, Fábio Sadao (2008)
This doctorate thesis tries to understand how spacialitites are built in cinema and television. Based on this main problem, other related issues are also studied: the existing relationships between space constructibility and audiovisual montage; the way movie spacialities communicate with television constructibilities and the communicative relations established between the studied spacialities and the viewer. Consequently, the main objective of this study is to contribute to research on space organization forms in media systems and on the ways these construction provide senses. Thus, the study is related to others whose study object is spacialities, aiming to investigate analysis categories that may clear out their articulation forms. The analysis corpus is divided into two groups. The first one, related to cinema, consists of two movies: A ostra e o vento (Walter Lima Jr./1997) and Elephant (Van Sant/ 2003). The second one, related to television, consists of the first journey of the micro series Hoje é dia de Maria, directed by Luiz Fernando Carvalho, in 2005. The main methodological analysis strategy is the comparative reading of the texts through ordering forms of montage spacialities. Among them, the comparative analysis allows detecting different forms of space design and also helps the perception and understanding of contamination borders between languages. In order to do the reading and investigation of the analysis corpus, this study uses the space analysis categories spatiality, visuality, visibility and communicability - proposed by Prof. Dr. Lucrécia D Alessio Ferrara; the concept of montage studied by the Russian movie maker Sergei Eisenstein; the notions of border, cultural text, memory and intelligent dispositive among system proposed by Iuri Lotman; and also the notions of image, diagram and metaphor studied by semioptician Charles Sanders Peirce. Due to the proposed theme, this idea interweaving is fundamental to understand how the space is thought of and ordered in montage through the existing conflicting spacialities among sign and cultural cells